Implementasi Business Intelligence untuk Visualisasi Data Akademik Menggunakan Power BI Dalam Meningkatkan Kualitas Layanan Akademik: - - Vera Wijaya; Tongam E. Panggabean (Universitas Budi Darma, 2026)
Improving the quality of higher education requires the effective, integrated, and measurable management and analysis of students’ academic data. However, many higher education institutions still face challenges in collecting, integrating, and analyzing academic data efficiently. Consequently, the monitoring of academic performance has not yet been conducted in a standardized manner and has not fully supported the achievement of additional performance indicators. In this context, the implementation of Business Intelligence (BI) is highly relevant, as it provides a systematic platform for managing students’ academic performance data and presenting it through informative visualizations. This study aims to implement a Business Intelligence system using Power BI architecture to integrate and manage students’ academic performance data obtained from various academic sources. The data used in this study consisted of 80 student records, including grades, semester grade point average, cumulative grade point average, academic status, study program, and cohort year for the 2023 - 2024 period. The data integration process was carried out through the stages of extraction, transformation, and loading into the Power BI model. The implementation results show that the system was able to process 98% of the available academic data and generate three interactive dashboards, including visualizations of GPA trends, student attendance distribution, and student grade distribution. Based on the testing results, the use of the Power BI dashboard improved the efficiency of the academic reporting process from three days to one hour, representing an increase of 93.1%. In addition, the level of conformity between the information displayed on the dashboard and the source data achieved an accuracy of 97.5%, indicating that the system can support information validity in the academic decision-making process. The implementation of Business Intelligence contributes to improving academic data management, accelerating the monitoring of student achievement, assisting stakeholders in interpreting data more effectively, and supporting the enhancement of academic service quality and higher education performance evaluation.